The Influence Of Promotion, Brand Image, And Advertising Attractiveness Through Instagram Media Social On Buying Decisions Of Namaste Resto Indonesia - Excel Excel; Ilona Vicenovie Oisina Situmeang (Publikasi Indonesia, 2023)
This study aims to find out how much influence the variables are researched and studied by researchers, and also to prove that purchasing decisions that occur at namaste restaurants are influenced by some of the variables above, such as Advertising Attractiveness, Promotio, and Brand Image through instagram media social. The type of research used in this study is quantitative, where later there will be the use of important data that can be used as evidence or validation of data that will later be used for this thesis. This research will later use as many as 100 correspondents to be surveyed at the location of the Indonesia restaurant namaste, and the data obtained will later be processed into new data that is accurate and can be accounted for for its validity.